Pengaruh Kecepatan Kendaraan Terhadap Tingkat Kerusakan Jalan Menggunakan Metode PCI (Pavement Condition Index) - eko prayitno (Jurnal Ilmiah Rekayasa Sipil, 2020)
The pavement and pavement structure are structure consisting of one or several layers of processed materials, whose the function is to support the weight of the traffic load without causing significant damage to the construction. Pavement Condition Index (Pavement Condition Index) is the level of pavement surface condition and its size in terms of the power function that refer to the conditions and damage on the pavement surface that occurs. The Pavement Conditions Index or PCI is a numerical index that has values ​​ranging from 0 to 100 with criteria excellent, very good, good, fair, poor, very poor, and failed. The field study of this research is the road section starting from STA 310 + 000 up to 320 + 000. The assessment of road conditions according to the Pavement Condition Index (PCI), where the data was collected through field surveys. The types of damage on the ivory tip of the STA 310 + 000 - 320 + 000 are patches, crocodile cracks, holes, edge cracks, loose grains, waves and elongated cracks. Obtained pavement condition index (PCI) average is 34.6 with an assessment of the condition of road damage is bad (poor). Based on the PCI value the road is included in the periodic maintenance program.